2015
DOI: 10.1002/ptr.5410
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and Botanical Medicines: An Overview

Abstract: Constipation affects 14% of the adult population globally, mainly women, and significantly impacts on health-related quality of life. The causes of constipation are mainly three: lifestyle related (functional constipation), disease related, and drug induced. Constipation can generate considerable suffering, including abdominal pain and distension, anorexia, and nausea. The value of some therapeutic measures such as increased fluid intake, physical activity, diet rich in fiber, and nutritional supplements recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 41 publications
0
62
0
2
Order By: Relevance
“…In a previous randomized double-blind study, Ma-zi-ren-wan was shown to be safe and effective at alleviating functional constipation [42]. One of the commonly prescribed single herb, Radix et Rhizoma Rhei, was also a commonly used laxative [43]. Other herbal formulas such as Liu-wei-di-huang-wan was used for improving osteoporosis [44] and Shao-yao-gan-cao-tang for relieving muscle spasm [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous randomized double-blind study, Ma-zi-ren-wan was shown to be safe and effective at alleviating functional constipation [42]. One of the commonly prescribed single herb, Radix et Rhizoma Rhei, was also a commonly used laxative [43]. Other herbal formulas such as Liu-wei-di-huang-wan was used for improving osteoporosis [44] and Shao-yao-gan-cao-tang for relieving muscle spasm [45].…”
Section: Discussionmentioning
confidence: 99%
“…According to the compatibility principle of TCM, rhubarb is the principal drug in TWCQT [3]. Rhubarb is officially listed in the Chinese, European, and Japanese Pharmacopoeia, commonly used in TCM prescriptions, as well as in self-medication for constipation in many countries [4]. Anthraquinones are reported to be the major active components present in rhubarb with wide pharmacological effects and some toxicity concerns [57].…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is a common gastrointestinal complaint clinically, affecting an estimated 12–19% of Americans, 14% of Asians and up to 27% of the global population [8, 9], and significantly impacts on health-related quality of life [10]. With an unfavorable response to current treatments, many patients in China seek help from TCM, mostly taking herbal medicine [9].…”
Section: Introductionmentioning
confidence: 99%